Analysis of covalent ellipticine- and doxorubicin-derived adducts in DNA of neuroblastoma cells by the ³²P-postlabeling technique - Stiborová, Marie; Poljaková, Jitka; Eckschlager, Tomáš; Kizek, René; Frei, Eva (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2012)
BACKGROUND: Ellipticine and doxorubicin are antineoplastic agents, whose action is based mainly on DNA damage such as intercalation, inhibition of topoisomerase II and formation of covalent DNA adducts. The key target to resolve which of these mechanisms are responsible for ellipticine and doxorubicin anticancer effects is the development of suitable methods for identifying their individual DNA-damaging effects. Here, the (32)P-postlabeling method was tested to detect covalent DNA adducts formed by ellipticine and doxorubicin. METHODS: The standard procedure of (32)P-postlabeling assay, this procedure under ATP-deficient conditions, the version using extraction of adducts with n-butanol and the nuclease P1 enrichment version were used to analyze ellipticineand/ or doxorubicin-derived DNA adducts. RESULTS: Two covalent ellipticine-derived DNA adducts, which are associated with cytotoxicity of ellipticine to human UKF-NB-3 and UKF-NB-4 neuroblastoma cell lines, were detected by the (32)P-postlabeling method. These adducts are identical to those formed by the ellipticine metabolites, 13-hydroxy- and 12-hydroxyellipticine. In contrast, no covalent adducts formed by doxorubicin in DNA of these neuroblastoma cells and in DNA incubated with this drug and formaldehyde in vitro were detectable by the (32)P-postlabeling assay. CONCLUSIONS: The results presented in this paper are the first to demonstrate that in contrast to covalent DNA adducts formed by ellipticine, the adducts generated by formaldehyde-mediated covalent binding of doxorubicin to DNA are not detectable by the (32)P-postlabeling assay. No DNA adducts were, detectable either in vitro, in incubations of DNA with doxorubicin or in DNA of neuroblastoma cells treated with this drug. The results also suggest that covalent binding of ellipticine to DNA of UKF-NB-3 and UKF-NB-4 neuroblastoma cell lines is the predominant mechanism responsible for the cytotoxicity of this drug. To understand the mechanisms of doxorubicin anticancer effects on neuroblastoma cells, development of novel methods for identifying covalent doxorubicin-derived DNA adducts is the major challenge for further research.
Keywords: doxorubicin; Antineoplastic Agents; adukty DNA; Neuroblastoma; lidé; elipticiny; neuroblastom; Cell Line, Tumor; protinádorové látky; DNA Adducts; Doxorubicin; Isotope Labeling; Ellipticines; Humans; Phosphorus Radioisotopes; izotopové značení; nádorové buněčné linie; radioizotopy fosforu